Surface-initiated controlled polymerization as a convenient method for designing functional polymer brushes: From self-assembled monolayers to patterned surfaces - Olivier, Aurore; Meyer, Franck; Raquez, Jean-Marie; Damman, Pascal; Dubois, Philippe (Progress in polymer science, 2012)
Surface-functionalization mediated through “grafting from” methods is of considerable interest as means to tailor the chemical and physical properties of functional substrates in a reliable way. The resulting polymer brushes, obtained by a “grafting from” strategy, are composed of grafted polymer chains tethered from one of their extremities to a surface by a covalent bond. Tuning the molecular parameters of these polymeric brushes such as the nature of monomer, the grafting density, and the chain length as well as the design of micropatterned structures enables delicate modification of the properties of these substrates, paving the way to the development of functional surfaces. In this review, we highlight recent and most important approaches to form monolayers and to subsequently elaborate homogeneous and heterogeneous coatings of polymer brushes by surface-initiated polymerization. The control of initiator molecule assembly is particularly important for the final configuration of polymer brushes. We report the creation of homopolymers and block copolymers using major controlled polymerization techniques as well as lithographic techniques aiming at the design of polymeric (micro- or nano-) patterns.